2019
DOI: 10.1158/1078-0432.ccr-18-2748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Concomitant Administration of Gastric Acid–Suppressive Agents and Pazopanib on Outcomes in Soft-Tissue Sarcoma Patients Treated within the EORTC 62043/62072 Trials

Abstract: Purpose: Pazopanib is active in soft-tissue sarcoma (STS). Because pazopanib absorption is pH-dependent, coadministration with gastric acid-suppressive (GAS) agents such as proton pump inhibitors could affect exposure of pazopanib, and thereby its therapeutic effects. Patients and Methods: The EORTC 62043 and 62072 were single-arm phase II and placebo-controlled phase III studies, respectively, of pazopanib in advanced STS. We first compared the outcome of patients treated with pazopanib with or without GAS ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…Other studies defined a threshold for duration of clinically meaningful overlap between ASMs and TKIs ranging from 20−80% . In this study, we did not set a predefined threshold for percent overlap and instead included any duration of concomitant ASM use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies defined a threshold for duration of clinically meaningful overlap between ASMs and TKIs ranging from 20−80% . In this study, we did not set a predefined threshold for percent overlap and instead included any duration of concomitant ASM use.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with STS in particular, Mir et al 11 reported in abstract form that of 333 European patients with STS retrospectively analyzed from the European Organization for Research and Treatment of Cancer (EORTC) 62043/62072 trials, 117 patients received concomitant ASMs with PAZ, and median PFS was shorter in the concomitant acid suppressive group vs. the no ASM group (2.8 months vs. 4.6 months; P = 0.008). Our study supports these findings, but is also the first to describe the real-world use of PAZ with concomitant ASM and counseling as to appropriate timing in a non-European cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported shorter PFS and overall survival (OS) in patients treated with pazopanib receiving concomitant pH‐elevating medication, though in one of these studies the effect on treatment outcome was not statistically significant . Unfortunately, no pazopanib plasma concentrations were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies reported shorter PFS and overall survival (OS) in patients treated with pazopanib receiving concomitant pH-elevating medication, though in one of these studies the effect on treatment outcome was not statistically significant. 148,149 Unfortunately, no pazopanib plasma concentrations were measured. However, considering the essential role of gastric pH in the absorption of pazopanib and the previously established decrease in pazopanib AUC when combined with a proton pump inhibitor, it is likely that the shortened survival is caused by underexposure to pazopanib.…”
Section: Gastric Phmentioning
confidence: 99%